Surgical strategies for patients with congenital heart disease and severe pulmonary hypertension in low/middle-income countries. Issue 2 (9th October 2015) - Talwar, Sachin; Keshri, Vikas Kumar; Choudhary, Shiv Kumar; Gupta, Saurabh Kumar; Ramakrishnan, Sivasubramanian; Juneja, Rajnish; Saxena, Anita; Kothari, Shyam Sunder; Airan, Balram
Abstract : In this review, we discuss specific surgical strategies that are used in patients with congenital heart disease and severe pulmonary arterial hypertension. Our own experience, with the use of unidirectional valved patches in managing these patients, is also discussed in detail.